Biopolymeric Films of Amphiphilic Derivatives of Chitosan: A Physicochemical Characterization and Antifungal Study - Rodrigues Santos Alves, Anna Carolina [UNESP]; Furuyama Lima, Aline Margarete [UNESP]; Tiera, Marcio Jose [UNESP]; Oliveira Tiera, Vera Aparecida de [UNESP] (Mdpi, 2019)
The chemical modification of chitosan has been an active subject of research in order to improve the physicochemical and antifungal properties of chitosan-based films. The aim of this study was to evaluate the physiochemical and antifungal properties of films prepared with chitosan and its derivatives containing diethylaminoethyl (DEAE) and dodecyl groups (Dod). Chitosans and selected derivatives were synthesized and characterized, and their films blended with glycerol and sorbitol (5%, 10%, and 20%). They were studied by means of the evaluation of their mechanical, thermal, barrier, and antifungal properties. The collected data showed that molecular weight (Mw), degree of acetylation, and grafting with DEAE and Dod groups greatly affected the mechanical, thickness, color, and barrier properties, all of which could be tailored by the plasticizer percentage. The antifungal study against Aspergillus flavus, Alternaria alternata, Alternaria solani, and Penicillium expansum showed that the films containing DEAE and Dod groups exhibited higher antifungal activity than the non-modified chitosans. The mechanical properties of highly soluble films were improved by the plasticizers at percentages of 5% and 10%, indicating these derivatives as potential candidates for the coating of seeds, nuts and fruits of various crops.
Keywords: chitosan; derivatives; films; antifungal activity; coating; edible films